14-3-3η protein: a promising biomarker for rheumatoid arthritis. (19th July 2018) - Zeng, Tingting; Tan, Liming
Effective management of rheumatoid arthritis (RA) depends on early identification followed by timely invention and proper monitoring of treatment responses which remain challenges facing rheumatologists for lacking biomarkers of high sensitivity and specificity. 14-3-3η has been reported to be a novel RA-related biomarker inducing the expression of multiple factors mediating the pathogenesis of RA, and increasing the diagnostic capture when combined with rheumatoid factor and anticyclic citrullinated peptide antibody. Besides, elevated serum 14-3-3η was relevant to more serious joint erosion and worse therapy outcomes. Here, we summarized the emerging knowledge regarding the roles 14-3-3η plays in RA and its clinical implications as diagnostic, prognostic and therapeutic response surrogate as well as potential drug target for RA.